Enhancing Arabic Vocabulary Mastery through Kahoot: Evidence from Elementary Madrasah Students - Zaki, Mohammad (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Previous studies on technology-enhanced Arabic language learning have predominantly focused on general applications or higher education levels, leaving a significant gap regarding interactive, game-based tools for vocabulary acquisition at the primary Islamic school (Madrasah Ibtidaiyah/MI) level. This study investigates the effectiveness of interactive, game-based digital media, specifically Kahoot!, in developing Arabic vocabulary among fifth-grade students at Madrasah Ibtidaiyah. Addressing the identified gap, the research employs a quantitative approach, utilizing pre-test and post-test measurements. The results demonstrate a significant increase in learning outcomes, with the average score rising from 30.90 (pre-test) to 80.00 (post-test). Statistical analysis (t-test, t-value = 11.260 > t-table 1.721, df=21) confirms that the use of Kahoot! positively and significantly enhances students' Arabic vocabulary mastery. The findings indicate that this method successfully boosts student enthusiasm and active participation. Consequently, Kahoot! is recommended as an effective and innovative alternative medium for Arabic vocabulary learning at the primary Islamic school level.